The Necessity and Importance of Research and Its Role in Afghan Society - Yar, Fayaz Gul Mazloum (Syntax Corporation, 2024)
This research examines the necessity and importance of scientific research in Afghan society and its role in the country's economic, social, and cultural development. Given Afghanistan's numerous challenges, including war, poverty, and political instability, research is recognized as a vital tool for identifying and analyzing problems and providing data-driven and evidence-based solutions. The research employs a qualitative methodology based on semi-structured interviews with researchers, university professors, and policymakers. Findings indicate that scientific research can contribute to economic development by enhancing educational quality, improving infrastructure, and increasing innovation. Additionally, the results suggest that institutional, cultural, and financial resource barriers are among the main challenges to advancing research in Afghanistan. Ultimately, this study emphasizes the need for investment in research and the creation of suitable infrastructures to achieve sustainable development and improve the quality of life in Afghanistan.